Draft Genome Sequences of Marinobacter similis A3d10(T) and Marinobacter salarius R9SW1(T) - Ivanova, Elena P. (American Society for Microbiology, 2014)
Here, we present the draft genomes of Marinobacter similis A3d10(T), a potential plastic biodegrader, and Marinobacter salarius R9SW1(T), isolated from radioactive waters. This genomic information will contribute information on the genetic basis of the metabolic pathways for the degradation of both plastic and radionuclides.